Electrical Insulation Tape Winding and Inspection System. (17th November 2019) - Petrella, Joseph R.; D'Agostino, Michael J.; Cropper, Mark; Guttenfelder, Jessica
Abstract: An electrical insulation web winding and optical inspection system has been developed to provide semiautomatic material handling and machine vision inspection of composite electromagnet coil insulation materials. Composite electrical insulation for electromagnet conductor insulation typically comprises a nonconductive woven filler (typically S-Glass), nonconductive film (typically Kapton®), and fixating resin. Prior to the subject system, the stock woven filler and film used to assemble the composite structure were inspected manually for dimensional and foreign matter presence, which did not provide 100% inspection. The subject system features a web handling reel-to-reel transfer mechanism that includes an open-loop web positional alignment device to maintain the web centerline position. A machine vision system is used to optically inspect passing web materials for dimensional defects and foreign materials. This system is capable of inspection of single web woven filler material and/or colaminated woven filler material and nonconductive film. A detected defect automatically terminates web movement, generates an alarm, and records images of the defects on a media storage device. Prototype material inspections performed by the subject machine on approximately 21 567 m (70 759 ft) of material detected 174 pieces of debris.